Sustainable production of pineapples on tropical peat soils - Haruna, Ahmed Osumanu; Mohd Hanif, Ahmad Husni; Abd Rahim, Anuar; Musa, Mohamed Hanafi (Universiti Putra Malaysia Press, 2013)
This book contains information on pineapples cultivation on tropical peat soil and it discusses some essential elements for sustainable cultivation of pineapples on this type of organic soils. Therefore, the book is designed as a quick reference text, with the aim that farmers, students and scientists with little experience on pineapples cultivation on organic soils are able to grasp the rudiments of their cultivation on these soils. This book will also be of significant interest to those working in the applied sciences.